Visual Scanning Training for Neglect after Stroke with and without a Computerized Lane Tracking Dual Task - Van Kessel, M.E.; Geurts, A.C.H.; Brouwer, W.H.; Fasotti, L. (Frontiers in Human Neuroscience, 2013)
Neglect patients typically fail to explore the contralesional half-space. During visual scanning training, these patients learn to consciously pay attention to contralesional target stimuli. It has been suggested that combining scanning training with methods addressing non-spatial attention might enhance training results. In the present study, a dual task training component was added to a visual scanning training (i.e. Training di Scanning Visuospaziale – TSVS; Pizzamiglio et al., 1990). Twenty-nine subacute right hemisphere stroke patients were semi-randomly assigned to an experimental (N=14) or a control group (N=15). Patients received 30 training sessions during six weeks. TSVS consisted of four standardized tasks (digit detection, reading/copying, copying drawings and figure description). Moreover, a driving simulator task was integrated in the training procedure. Control patients practiced a single lane tracking task for two days a week during six weeks. The experimental group was administered the same training schedule, but in weeks 4-6 of the training, the TSVS digit detection task was combined with lane tracking on the same projection screen, so as to create a dual task (CVRT-TR). Various neglect tests and driving simulator tasks were administered before and after training. No significant group and interaction effects were found that might reflect additional positive effects of dual task training. Significant improvements after training were observed in both groups taken together on most assessment tasks. Ameliorations were generally not correlated to post onset time, but spontaneous recovery, test-retest variability and learning effects could not be ruled out completely, since these were not controlled for. Future research might focus on increasing the amount of dual task training, the implementation of progressive difficulty levels in the driving simulator tasks and further exploration of relationships between dual task training and daily functioning.